2019
DOI: 10.20471/may.2019.55.01.05
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Alcohol on Oral Health, a Review

Abstract: Drinking alcoholic beverages is one of the oldest socially acceptable forms of behavior which can lead to the development of alcohol addiction. Long-term alcohol drinking has, together with numerous psychological and somatic complications, harmful consequences for the oral health. Patients suffering from alcoholism generally have poorer oral hygiene, dental care, periodontal status, fewer teeth, more carious lesions, gingival diseases, inter-dental papillae bleeding and deep gingival pockets associated with bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 34 publications
(42 reference statements)
0
20
0
Order By: Relevance
“…High levels of alcohol present in the oral cavity due to binge drinking may alter the oral environment and lead to oral microbiome dysbiosis. Alcohol can cause the reduction of salivary glands as well as the reduction of the oral mucosa based on a previously conducted study 20 . These changes lead to the overall change in the oral pH, which allows the microbiome to shift from a healthy microbiome to the pathogenic microbiome 34 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…High levels of alcohol present in the oral cavity due to binge drinking may alter the oral environment and lead to oral microbiome dysbiosis. Alcohol can cause the reduction of salivary glands as well as the reduction of the oral mucosa based on a previously conducted study 20 . These changes lead to the overall change in the oral pH, which allows the microbiome to shift from a healthy microbiome to the pathogenic microbiome 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that alcohol metabolism takes place mainly in the liver, studies have found that the level of a byproduct of alcohol metabolism, acetaldehyde, is higher in saliva than in the blood immediately after alcohol consumption while the concentration of alcohol in the saliva is equivalent to the blood alcohol within thirty minutes of consumption 19 . This leads to the accumulation of toxic molecules like acetaldehyde that damage the mucosal and glandular tissues 20 . The damaged mucosa causes an impairment of the immune function that may lead to microbial infection and changes to the oral microbiome 20 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among those well described are vitamin deficiencies, which may support a dramatic worsening of ethanol-related pathological conditions. A wide range of presentations related to vitamin deficiencies in alcohol consumers may be visible in the oral cavity, such as inflammatory changes, hemorrhages, ulcers, precancerosis, sensory presentations, or salivary gland problems [ 122 ]. Alcohol consumption decreases the transport of thiamine (vitamin B1) across the intestinal mucosa, decreases the storage of thiamine in the liver, and impairs the activation by inhibiting thiamine phosphorylation to thiamine diphosphate [ 123 ].…”
Section: Toxicity Of Ethanolmentioning
confidence: 99%
“…Similarly, this “drying effect” is on mucous surfaces of the mouth and upper part of the gastrointestinal tract after ingesting concentrated alcoholic beverages. About 30 min after alcohol ingestion, higher ethanol concentrations occur in saliva and salivary glands than in blood [ 122 ]. In short-term experiments, the direct local toxic action of the alcohol leading to damage of the mucous membrane proportional to the degree of alcohol concentration was proven [ 132 ].…”
Section: Toxicity Of Ethanolmentioning
confidence: 99%